Maximum Ride. [4] - Lee, NaRae (Yen Press, 2011)
Despite their initial hesitation, living with Anne has softened the Flock, so Max is keenly aware that it's time to leave. With Thanksgiving so near, though, all of them want to stay, at least until they've had their first ever Thanksgiving turkey! But danger is on the horizon as Jeb's plan advances, and while the Flock's new school seems normal and safe, secrets are hidden beneath its prestigious facade.